Contextual Projective Learning Model in Elementary School Science Education: An Analysis of the Learning Process and Student Engagement - Mareta Putri, Reza; Yola Shafarina, Annisa; Dwi Febriyanti, Elisa; Agis, Fathul (IJORER : International Journal of Recent Educational Research, 2025)
This study investigates the implementation of the Contextual–Projective Learning Model (KP) in elementary school science and its impact on student engagement and conceptual understanding, aiming to explore how contextual and project-based learning can foster meaningful learning experiences. The research was conducted at SD Aisyiyah Kalianda, focusing on the water cycle topic. A qualitative descriptive approach was employed, combining classroom observations, semi-structured interviews with teachers and students, and analysis of learning documentation. Data were analyzed thematically using Miles, Huberman, and Saldaña’s interactive model to identify patterns in the learning process and student engagement. Findings indicate that KP effectively transforms the learning environment from teacher-centered to student-centered, positioning students as active knowledge constructors. Students engaged in discussions, collaboratively planned and executed mini-projects, and presented outcomes, enhancing cognitive, social, emotional, and behavioral engagement. Conceptual understanding improved as students connected theoretical knowledge with practical observation. The approach also fostered 21st-century skills, including critical thinking, creativity, collaboration, and communication (4C skills). Challenges such as limited instructional time, varying student abilities, and constrained resources were mitigated through structured project planning, differentiated guidance, peer teaching, and creative use of simple, local materials. This study highlights the integration of contextual learning with project-based activities in elementary science, emphasizing simultaneous development of conceptual understanding and 21st-century skills, with the teacher acting as an active facilitator. The findings provide both theoretical insights into constructivist, student-centered learning and practical guidance for implementing effective, meaningful science education at the elementary level.